Shulaveri Neolithic Culture in Eastern Georgia - Khipshidze, Shorena ("Intercultural Dialogues" Transactions, 2023)
The research is about society’s development in the Neolithic Age, which is called “Neolithic Revolution” in archeology, it consists of VI-IV centuries B.C.. We paid special attention to the pre-farming monuments, Shulaveri and Imiri hills complexes in the Eastern Transcaucasia, known for the Shulaveri culture. We studied the features of the aforementioned culture and its significance in society’s development. We discussed the opinions based on which this culture depicts society’s Neolithic-Eneolithic ages. The establishment of the powerful pre-farming culture in Eastern Georgia, with its titles and range of characteristics, resulted in the controversies in scientists’ opinions. Shulaveri and Imiri hills, with layers and artefacts, have commonalities with Armenian and Azerbaijanian cultures. Several scientists’ concepts are discussed regarding the peculiarities of the Neolithic culture in the research, in terms of development we saw how different the situation is in Georgia, where the coexistence of pre-farming culture and three different cultures, also at certain levels, is identified. From those, Shulaver-Shomutepe and Sioni-Tsopi circle monuments have taken longer for development, while in the final level, how it is assumed, coexists Berikldeebi-Leilatepe culture. Primarily we paid special attention to this era’s society, including women’s cult. Shulaveri hill and other settlements signify that women held the leading position. The prioritisation of women’s role was encouraged by the transition to farming production (farming, cattle breeding and pottery). Today Shulaveri-Shomupete culture is not completely studied and it is to be considered that discovering and studying new artefacts will confirm its dating and significantly change scientists’ views. The most important Stone-coppers and Bronze Ages developed as the result of the Neolithic society.